Business Development Strategy for the Management of Used Cooking Oil as a Raw Material for Biodiesel - Trisa Oktavianti; Zenal Asikin; Linda Karlina Sari (Pelopor Publikasi Akademika, 2026)
This study examines the business development strategy of PT XYZ, a Used Cooking Oil (UCO) management company serving as biodiesel feedstock in Jakarta. The research background includes growing biodiesel demand driven by the B35 mandatory program and sustainability program. The significant potential of UCO as a more economical and environmentally friendly alternative feedstock, and the business challenges faced by PT XYZ following the 2022 UCO export restriction policy through the Domestic Market Obligation (DMO) mechanism, which caused an average export volume decline of 84% and temporary closure of three branches outside Jakarta. The study employs a qualitative-quantitative approach using Business Model Canvas (BMC), VRIO, PESTEL, Porter's Five Forces, IFE-EFE matrices, IE matrix, SWOT, and Analytical Hierarchy Process (AHP) using Expert Choice 11 softwere for strategy prioritization. Results indicate that PT XYZ's main strengths are its QC capabilities and laboratory UCO, strong reputation, strategic location in the Jabodetabek area, UCO collection network and access to capital. Minewhile, weaknesses include the absence of ISCC certification and market share analysis, limited development and digital systems for financial. Based on the IE matrix, PT XYZ is positioned in cell II (grow and build). Four recommended strategic priorities are: (1) medium-term contracts with buyers, (2) UCO collection network development, (3) operational cost efficiency, and (4) market expansion. The proposed new BMC integrates business process digitalization, market segment diversification to increase revenue sources, and gradual development toward self-exporting.